Competency requirements for process safety auditors. Issue 2 (26th May 2014) - Baybutt, Paul
<x xml:space="preserve">Abstract</x> Auditing is a critical aspect of a process safety program which ensures the program is designed appropriately and implemented properly. The competency of process safety auditors is essential for quality audits. The nature of process safety auditing is described to clarify the responsibilities of auditors. Suitable criteria for selecting process safety auditors to ensure their competency are identified and discussed. Criteria for lead auditors, team auditors, and audit teams are addressed. Also, performance metrics that can be used to judge the performance of process safety auditors are described. © 2014 American Institute of Chemical Engineers Process Saf Prog 34: 179–182, 2015